Konsep Pemenuhan Hak Atas Pangan Bagi Masyarakat Di Wilayah Perbatasan Pada Masa Pandemi Covid-19 - Luhulima, Yusran Baginda; Wattimena, Josina Augustina Yvonne; Peilouw, Johanis Steny Franco (PATTIMURA Legal Journal, 2023)
Introduction: The right to food is a very important right to fulfill, because without food, the survival and welfare of society cannot be realized. Purposes of the Research: Studying and knowing the concept of legal protection and fulfilling the right to food for people in border areas during the covid-19 pandemic. Methods of the Research: This study uses a normative legal research method with a descriptive analytical type of research. Results Originality of the Research: The results of the study show that the impact of the spread of the covid-19 pandemic has caused the fulfillment of the right to food for people in border areas to experience obstacles and is not fulfilled properly.